Cost control mechanism as procurement selection decision matrix for Malaysian infrastructure projects. Issue 1 (April 2020) - Romeli, N; Muhamad Halil, F; Ismail, F; Hasim, M S
Abstract: Malaysia was enumerated as the realm that retains a high quality of infrastructure facilities among the other ASEAN countries, and the number of infrastructure projects is progressively developed to offers a virtuous cordiality to the citizen. Inevitably, the infrastructure projects are barely devoted to the complex project selection decision phase where the procurement represents the suave configuration of the projects. However due to the difficulty in analyzing an assorted variety of procurement system afford by inexperienced decision maker the procurement route often unkempt the cost related dynamic. Regularly, the decision based on narrow consideration of cost and project quality overestimated in within a short period of construction. Even worst, there is partially public discourse on the cost control elements towards the disputable project procurement selection, which reflects the lesson learnt on the previous infrastructure project has mismanaged to provide a municipal cost precaution. Prior to that, the research objective is to identify the relationship in between the cost control mechanism and project procurement selection decision in infrastructure projects. The adoption of quantitative method and analysis applies in this research among the infrastructure expert settings. The output from the methods disclose that the cost control acquires a strong correlation in the project procurement selection decision equation with project risk, capital resources, alliance requirement based, changes of policy, fluctuation of inflation rates, labor cost, material cost, robust feasibility studies as a driver to an efficacious project procurement assortment verdict.